The Marble Statue as Idea Collected Essays on Adalbert Stifter's "Der Nachsommer" - Oertel Sjögren, Christine (UNC Studies in the Germanic Languages and Literatures, 1972)
Each of the nine essays in this illuminating study of "Der Nachsommer" focuses on heretofore overlooked details of the novel. As all the phenomena presented are oriented toward fulfillment of their highest potential, the novel emerges as a powerful assertion of the intent to achieve classical form in all things despite the ever-present threat of dissolution and chaos. With such emphasis upon the achievement of perfection, "Der Nachsommer" itself becomes a masterly exemplification of Stifter's concept Gestalt with its full ethical connotations.